Analysis of the contractor's performance during the Covid-19 pandemic in West Sumatra Province. Issue 1 (April 2021) - Syaferi, D O; Hidayat, B; Ophiyandi, T; Ferial, R
Abstract: The covid-19 pandemic had struck the world and affected the national development, especially in Indonesia. Many construction sectors experience disruption; therefore, it directly impacts the contractor's performance. This study analyzes the internal and external dominant factors that affect the contractor's performance during the covid-19 pandemic in West Sumatra Province, Indonesia. This study was a cross-sectional study with a qualitative approach using a self-administered questionnaire with 26 variables. Fifty eights respondents in the water resources field projects have participated in this study. The data was collected and analyzed by using multivariate analysis (logistic regression test). It was concluded that the distribution of salaries on the managerial aspect becomes dominant in the internal factor. Government policy factors regarding the implementation of work outside become the crucial external factor that significantly affects the contractor's performance. So, it is suggested to the well-organized distribution of salaries and well preparation of conditional administration related to government policies during the Covid-19 pandemic.